Development, implementation, evaluation and scaling-up of physical activity referral schemes in Germany: protocol for a study using a co-production approach. Issue 3 (22nd March 2021) - Weissenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus
Abstract : Introduction: Physical activity referral schemes (PARSs) are recommended to promote physical activity (PA) among adults at risk of developing or with established non-communicable diseases (NCDs). In Germany, this kind of referral schemes has not yet been implemented systematically and nationwide. In this study protocol, we present the methodological design of a co-production research study aimed at establishing a PARS for adults with NCDs in German primary healthcare. Methods and analysis: We will employ a co-production approach consistently throughout the four project phases: (1) development of the PARS; (2) preparation period; (3) implementation and evaluation; (4) development of a strategic plan for scaling up the PARS to the national level as part of standard care. The first phase will additionally include a status quo analysis of the existing physical activity pathways nationwide as well as an overview of international PARS models. A pragmatic trial design will be used for evaluating the developed PARS. The co-production approach will involve relevant actors in the German healthcare system, namely, healthcare service providers (eg, physicians, exercise professionals), health insurance providers, exercise providers, patients' representatives, experts in the development and implementation of educational concepts, and scientists from the fields of sports science and public health. Ethics and dissemination: The project has been reviewed and approved by the ethics committee of the Friedrich-Alexander-University Erlangen-Nürnberg (ethics approval number: 331_20 B). Through cooperation agreements, the stakeholders involved gave their consent to participate and were informed about the study in detail. The results of this study will be disseminated by international conference presentations and peer-reviewed publications, and if possible, a manual for the use of the PARS will be provided.